Design Of Ergonomic Tool Specification To Improve The Work Posture Of Operator In Workstation Of Mainboard Inspection In E-ktp Reader Production Process In Pt Abc Based On Rapid Upper Limb Assessment Method - Nur Intan Dhewanty Mayangsari; Wiyono Sutari; Marina Yustiana Lubis (eProceedings of Engineering, 2016)
PT ABC is one of the state-owned companies that produces electronic equipments such as electronic equipment for military, ICT (Information Communication Technology &), electronic equipment for navigation systems, electronic equipment for train, etc. In the production process flow there are 4 (four) inspection processes performed, one of them is mainboard ( GPIO & Cubie Board). Based on the observation in the field, the mainboard inspection process is still done manually and the operator works in a standing position with neck bend over to 17.080 of extension and the trunk is bending up to 45.180 of extension for 7 hours per day. All operators of mainboard inspection experience pain and discomfort in all parts of the body with different percentages. But the parts of the body that have the highest percentage of MSD risks about 10% are neck and legs. In this case the operator feel neck pain and feet pain. Based on Rapid Upper Limb Assesement (RULA) method, the RULA score obtained is 5 which means that the work posture requires analysis and improvement immediately. The RULA score is directly proportional to the risk of MSD, the higher the RULA score the higher also risk of Musculoskeletal Disorders (MSDs) is going. In mainboard inspection, operators only served to evaluate the soldering result by using a tool that is in the form of a magnifier which is equipped with a light that does not fit the operator’s need, instead it makes operators doing inspection in such work posture. The initial stage to solve the problem is gathering some data such as anthropometry data and the recommended work method which is doing inspection in sitting position and acommodated by ergonomic tool. Those data are used to design the specification of ergonomic tool. After designing, there will be the dimension specification of the workbench and the chair and also the specification of the magnifier. At last, the output of this research is RULA score of new work posture which is 3. Keywords : rapid upper limb assesment, specification, work posture, ergonomic tool, musculoskeletal disorders